Energy Consumption and ecology - Udías Vallina, Agustín (Razón y fe, 2022)
Man, at difference with other living beings consume a large quantity of energy for its multiple needs which increase with rise of world population and their development. This increase has speed up from the time of the industrial revolution. At present, the world year energy consumption is of 556 exajules, or 160,000 terawatts. From 1,800, the consumption has increased exponentially from 5600 to 160,000 terawatts, due to the increase in population from 1,000 to 7900 million, and the rise of material progress. In addition, energy consumption is very different into one country from others, it varies in kilowatts-hour from 26,500 for Norway to 180 for Nigeria. Thus, a direct relationship exists between energy consumption and the GDP of a country. Regarding the energy sources the 85% comes from fossil fuels so that their use has two negative effects: their depletion and the rise of pollution. However, at present there is a direct relationship between energy consumption, and quality of life. Rise in energy consumption has an impact in ecological problems. A Christian understanding of the problem according to the Laudato si’ of Pope Francis implies the need to use an integral ecology.